2004
DOI: 10.3168/jds.s0022-0302(04)73375-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Varying Gossypol Intake from Whole Cottonseed and Cottonseed Meal on Lactation and Blood Parameters in Lactating Dairy Cows

Abstract: Effects of varying amounts of gossypol from whole Upland cottonseed (WCS) and cottonseed meal (CSM) were evaluated in 40 midlactation Holstein cows. After 14 d of pretreatment, cows were assigned to 1 of the 5 treatments for 84 d: control (no gossypol), 931 mg/kg total gossypol (TG) and 850 mg/kg free gossypol (FG) from WCS (moderate TG and high FG); 924 mg/kg TG and 91 mg/kg FG from CSM (moderate TG and low FG), 945 mg/kg TG and 479 mg/kg FG with equal amounts of TG from WCS and CSM (moderate TG and FG), or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 20 publications
7
39
0
4
Order By: Relevance
“…However, there is evidence showing that part of gossypol escapes ruminal fermentation (Mena et al, 2004) and can affect animal health and performance (Risco et al, 2002). Effects of gossypol can lead to low hemoglobin and hematocrit levels (Velasquez-Pereira et al, 1999), osmotic fragility of erythrocyte, decrease in cell antioxidant power (Risco et al, 2002), productive performance (Santos et al, 2003;Villaseñor et al, 2008), milk production and breathing rate and finally death (Lindsey et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence showing that part of gossypol escapes ruminal fermentation (Mena et al, 2004) and can affect animal health and performance (Risco et al, 2002). Effects of gossypol can lead to low hemoglobin and hematocrit levels (Velasquez-Pereira et al, 1999), osmotic fragility of erythrocyte, decrease in cell antioxidant power (Risco et al, 2002), productive performance (Santos et al, 2003;Villaseñor et al, 2008), milk production and breathing rate and finally death (Lindsey et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results are reported in the literature regarding the production of dairy cows supplemented with different protein sources such studies reveal since no significant effect (BERNARD, 1997;PINA et al, 2006;MENA et al, 2001;MENA et al, 2004. ) to the linear decrease of milk production with the inclusion of bean residues (MAGALHÃES et al, 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Willard et al (1995) found that toxic effects of gossypol were much greater in nonruminants than in ruminants due to the fact that FG is binding with soluble proteins or amino acids in the rumen. However, numerous studies have shown that BG may be released as FG during the digestion period and then can be absorbed by the digestive tract (Blackwelder et al, 1998;Mena et al, 2004). Furthermore, broiler chickens fed extruded CSM still show poor growth performance, even though the extrusion process greatly decreased FG but not TG concentration (Gadelha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Mena et al (2004) suggested that the amounts of TG besides FG should be considered when determining a safe dairy cow feeding with products containing available gossypol.…”
Section: Introductionmentioning
confidence: 99%